IMPLEMENTASI METODE EDUTAINMENT PADA PEMBELAJARAN SKI DALAM MENUMBUHKAN RESPONSIF SISWA DI MTS YAYASAN PENDIDIKAN ISLAM (YPI) DELITUA - Jihan Ufairoh; Khairuddin Lubis; Hotni Sari (HIBRUL ULAMA, 2025)
the aim of this research is to determine: 1) The application of edutainment methods in learning the history of Islamic culture at MTS Islamic Education Foundation (YPI) Delitua. 2) Obstacles faced when implementing edutainment methods at MTS Islamic Education Foundation (YPI) Delitua. The method used in this research is qualitative descriptive research. Data collection techniques are observation, interviews and documentation. The data analysis technique used is the Miles and Huberman model, namely through data collection, data reduction, data presentation, and drawing conclusions. To obtain data whose validity can be accounted for, technical triangulation and source triangulation are used. Edutainment is a strategy that combines education with entertainment so that learning becomes fun, such a learning atmosphere can trigger the effectiveness of achieving learning goals. The results of this research show that learning using edutainment methods has a positive impact in increasing student responsiveness at MTS YPI Delitua. This can be seen from the increase in students' understanding of the material presented by the teacher. Edutainment methods can help improve students' memory regarding the material taught by the teacher. During the learning process through the implementation of the edutainment method, students were seen to be very enthusiastic when learning the history of Islamic culture.